2017
DOI: 10.1111/maec.12443
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic diversity of marine gastropod Monodonta labio (Trochidae): did the early Pleistocene glacial isolation and sea surface temperature gradient jointly drive diversification of sister species and/or subspecies in the Northwestern Pacific?

Abstract: Formation of glacial refugia during the Pleistocene climatic oscillations has been put forward to elucidate the diversification of marine organisms in the north‐western Pacific. The marine gastropod Monodonta labio is one of the most common species in the Northwestern Pacific and possibly possesses cryptic diversity. Here, we investigate the phylogeographic pattern of this species to test the potential mechanisms driving its diversification in the Northwestern Pacific. Genetic information for two mitochondrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 70 publications
(92 reference statements)
7
29
1
Order By: Relevance
“…Revealing patterns of phenotypic variation is the first step towards understanding the mechanisms of evolution and speciation. In this study, a pattern of divergence in shell shape among different populations of Monodonta labio was identified, with the most marked divergence in shell shape between two major genetic groups (Clade A + B + C and Clade D + E of Zhao et al ., 2017). In a previous study (Takenouchi, 1985), morphological diversity of this species was also reported in Japan.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Revealing patterns of phenotypic variation is the first step towards understanding the mechanisms of evolution and speciation. In this study, a pattern of divergence in shell shape among different populations of Monodonta labio was identified, with the most marked divergence in shell shape between two major genetic groups (Clade A + B + C and Clade D + E of Zhao et al ., 2017). In a previous study (Takenouchi, 1985), morphological diversity of this species was also reported in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Specimens of Monodonta labio shells used in this study belonged to the DNA-sequenced individuals used in the prior genetic study (Zhao et al ., 2017); specimens with damaged shells were excluded. The specimens used in this study were randomly collected from different microhabitats (rocky, cobble and boulder shores) in all populations at summer.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations